Hemograma y mielograma de los embriones de pollo - Pennimpede, Francisco C. (1949)
Fil: Pennimpede, F. C. Ministerio de Salud Pública de la Nación; Instituto Bacteriológico "Dr. Carlos G. Malbrán"; Argentina